Report of two cases of exfoliative chelitis and brief literature review - Fernandes, Tania Moreno; Barreto, Tathyane Trajano; Barreto, Bruno Nascimento (Journal of Oral Diagnosis, 2020)
Exfoliative cheilitis is a rare skin disease that there is not consensus about its pathophysiology, clinical course and treatment. It can cause functional and aesthetic problems, being associated with psychiatric and/or emotional disorders. Our objective is to report two cases of patients with exfoliative cheilitis and provide records to the limited literature. Results obtained with Prednisone, lip balm, fluid extract of Chamomila recutita and Dexpanthenol, associated with Imipramine Hydrochloride were satisfactory. Two years later, there was no relapse of the clinical picture in both patients, even without any treatment.